PENGARUH SELERA KONSUMEN DAN DIFERENSIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN CAT NIPPON PADA TOKO ERA BANGUNAN - Sri Ayu Ningtias; Nofal Supriaddin; La Ode Hamida (Sigma: Journal of Economic and Business, 2022)
This study aims to determine the effect of consumer tastes and product differentiation on purchasing decisions in the Building Era. The population in this study amounted to 96 obtained by accidental sampling technique. The type of data used in this research is quantitative data. Based on the research conducted, the research results show that simultaneously the variables of consumer taste and product differentiation have a positive and significant effect on purchasing decisions. Partially, consumer tastes have a positive effect on purchasing decisions and partially product differentiation has a positive and significant effect on purchasing decisions in the Building Era.